conditions of possibility of veil of ignorance from Sartrean Existentialism - Torres Ramis, Luis Alfonso (2016)
John Rawls proposes in his book The Theory of Justice, the principles of justice to promote a more just social system. To this raises the original position as hypothetical scenario in which a group of people, under the veil of ignorance, they would find the most appropriate principles of justice for society. The aim of this paper is to analyze the conditions of possibility of the veil of ignorance and so assess if it can be recognized as a proper strategy to propose the principles of justice. For this, some concepts are considered Sartrean existentialism.